The Effect of Entrepreneurial Orientation on Market Share of Consumer Goods Manufacturing Companies in Nigeria - Okusanya Adedoyin; Keinde Taiwo; Adenugba Olubunmi; Obisanya Adedoyin (Universitas Pendidikan Ganesha, 2024)
In the highly competitive consumer goods industry in Nigeria, achieving a dominant market share is a crucial factor for long-term business success. This study aims to analyze the impact of entrepreneurial orientation on the market share of specific consumer goods companies listed in Nigeria. The research adopts a cross-sectional survey design, involving 568 respondents selected from the target population. Data were collected using a validated structured questionnaire, with reliability test results showing Cronbach's alpha values ranging from 0.721 to 0.892. A response rate of 90.5% was achieved. Data analysis was conducted using multiple regression to identify the relationships between components of entrepreneurial orientation—creativity, competitive aggressiveness, proactiveness, risk-taking, and planning flexibility—and market share. The findings reveal that all components of entrepreneurial orientation have a significant impact on market share (Adj. R² = 0.791; F(5,441) = 339.129; p < 0.001). These results underscore the importance of entrepreneurial orientation in enhancing company performance. The study recommends that company managers integrate entrepreneurial strategies for more effective decision-making, target achievement, and performance optimization. The implications of this research are expected to support the sustainability of company performance in Nigeria's consumer goods industry.